The phn Island: A New Genomic Island Encoding Catabolism of Polynuclear Aromatic Hydrocarbons - Hickey, William J.; Chen, Shicheng; Zhao, Jiangchao (Frontiers in Microbiology, 2012)
Bacteria are key in the biodegradation of polycyclic aromatic hydrocarbons (PAH), which are widespread environmental pollutants. At least six genotypes of PAH-degraders are distinguishable via phylogenies of the ring-hydroxylating dioxygenase (RHD) that initiates bacterial PAH metabolism, and a given genotype has a characteristic taxonomic distribution. The latter pattern implies each genotype may have distinct pathways for horizontal gene transfer (HGT). But, while such processes are important in the function of PAH-degrader communities, mechanisms of HGT for most RHD genotypes are unknown. Here, we report in silico and functional analyses of the phenanthrene-degrader Delftia sp. Cs1-4, a representative of the phnAFK2 RHD group. The phnAFK2 genotype predominates PAH degrader communities in some soils and sediments, but, until now, their genomic biology has not been explored. In the present studies, genes for the entire phenanthrene catabolic pathway were discovered on a novel ca. 232 kb genomic island (GEI), now termed the phn island. This GEI had characteristics of an integrative and conjugative element with a mobilization/stabilization system similar to that of SXT/R391-type GEI. But, it could not be grouped with any known GEI, and was the first member of a new GEI class. The island also carried genes predicted to encode: synthesis of quorum sensing signal molecules, fatty acid/polyhydroxyalkonate biosynthesis, a type IV secretory system, a PRTRC system, DNA mobilization functions and > 50 hypothetical proteins. The 50% G+C content of the phn gene cluster differed significantly from the 66.7% G+C level of the island as a whole and the strain Cs1-4 chromosome, indicating a divergent phylogenetic origin for the phn genes. Collectively, these studies added new insights into the genetic elements affecting the PAH biodegradation capacity of microbial communities specifically, and the potential vehicles of HGT in general.